2003
DOI: 10.1071/bt02080
|View full text |Cite
|
Sign up to set email alerts
|

A new type of Kranz anatomy in Asteraceae

Abstract: The anatomical structure of the leaves and stems of the 13 species of Isostigma (Asteraceae: Heliantheae) has been examined by using light microscopy. All species of Isostigma have Kranz anatomy in their leaves, containing one or more Kranz units (=KU, the unit constituted by the vascular bundle/s, the parenchyma sheath and the surrounding mesophyll). It is demonstrated that there are the following two different types of Kranz anatomy in leaves of Isostigma: (1) Eryngiophyllum type, with one KU per leaf and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
(41 reference statements)
3
23
0
Order By: Relevance
“…The other anatomical categories among the C4 eudicots and that not examined in our study are: the ''Isostigma type'' demonstrated by certain species of the genus Isostigma (Heliantheae lineage, Asteraceae) (Peter and Katinas, 2003), the conospermoid type (Freitag and Stichler, 2000; the schoberia type according to Kadereit et al, 2003) found in Suaeda acuminata (Suaedoideae II lineage, Chenopodiaceae), and the two versions of single-celled-C 4 photosynthesis exhibited by two distinct lineages (Borszczowia and Bienertia) in the Suaedoideae tribe of the Chenopodiaceae (see Edwards et al, 2004 for a detailed review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other anatomical categories among the C4 eudicots and that not examined in our study are: the ''Isostigma type'' demonstrated by certain species of the genus Isostigma (Heliantheae lineage, Asteraceae) (Peter and Katinas, 2003), the conospermoid type (Freitag and Stichler, 2000; the schoberia type according to Kadereit et al, 2003) found in Suaeda acuminata (Suaedoideae II lineage, Chenopodiaceae), and the two versions of single-celled-C 4 photosynthesis exhibited by two distinct lineages (Borszczowia and Bienertia) in the Suaedoideae tribe of the Chenopodiaceae (see Edwards et al, 2004 for a detailed review).…”
Section: Discussionmentioning
confidence: 99%
“…Outside the Chenopodiaceae (C4 species of Salsola and close relatives, Pyankov et al, 2001b), this type is found in Asteraceae (Chrysanthellum) (Brown, 1975;Peter and Katinas, 2003; based on our criteria for anatomical type delineation) and Polygonaceae (Calligonum) (Winter et al, 1977;Voznesenskaya and Gamaley, 1986;Pyankov et al, 1994Pyankov et al, , 2000a. These studies and our own observations confirmed the occurrence of the salsoloid type amongst five distinct eudicot lineages; of these, two lineages are NADP-ME, while two lineages are NAD-ME (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on C 4 photosynthesis have been largely focused on species which form Kranz anatomy with two chlorenchyma layers surrounding each vein (called a multiple simple Kranz unit by Peter and Katinas, 2003), as occurs in C 4 monocots and numerous C 4 eudicot species. However, among C 4 eudicots, there are nine types of Kranz anatomy with two concentric chlorenchyma layers surrounding all veins (single compound Kranz unit according to Peter and Katinas, 2003); see Edwards and Voznesenskaya (2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, among C 4 eudicots, there are nine types of Kranz anatomy with two concentric chlorenchyma layers surrounding all veins (single compound Kranz unit according to Peter and Katinas, 2003); see Edwards and Voznesenskaya (2011). Among these is the Salsoloid type of anatomy which is characteristic for C 4 species in subfamily Salsoloideae.…”
Section: Introductionmentioning
confidence: 99%
“…The second strategy is represented by plants with "Kranz-type" structure, such as P. gardneri, which are efficient in maximizing photosynthesis under intense light. Whereas this anatomical mechanism is quite diffuse throughout Asteraceae, mainly present in the genus Pectis, it also occurrs in Isostigma, Chrysanthellum, and Flaveria (Solereder 1908;Smith & Turner 1975;Peter & Katinas 2003;Muhaidat et al 2007;Sage et al 2011). As widely reported, C 4 plants have an adaptive advantage over C 3 plants, since their water usage is twice as efficient, and they possess specific genetic differences that affect leaf anatomy, ultrastructure, and metabolic and energetic pathways (Metcalfe & Chalk 1979;Fahn & Cutler 1992;Hibberd & Covshoff 2010).…”
Section: Leaf Anatomymentioning
confidence: 99%